An Extraordinary Sulfonated‐Graphenal‐Polymer‐Based Electrolyte Separator for All‐Solid‐State Supercapacitors. Issue 36 (16th June 2016) - Liu, Xubo; Men, Chuanling; Zhang, Xiaohua; Li, Qingwen
Abstract : Sulfonated graphenal polymers can be assembled up by poly(vinyl alcohol) adhesion. The porous assembly structure results in a remarkably improved ionic conductivity and thus enhances electrochemical performances such as specific capacitance, capacitance retention, and cycling stability.